Effect of diisobutyl adipate on the expression of biomarker genes that respond to endocrine disruption and on gonadal sexual differentiation in Japanese medaka (Oryzias latipes) - Horie, Yoshifumi; Chihaya, Yuto; Yap, Chee Kong; Ríos, Juan Manuel; Ramaswamy, Babu Rajendran; Uaciquete, Dorcas (Elsevier, 2024)
Phthalate and non-phthalate plasticizers are used in polymer materials, such as plastic and rubber. It has recently been found that diisobutyl adipate (DIBA), which is considered an environmentally safe non-phthalate plasticizer, potentially acts as a thyroid disruptor in fish. Here, we investigated the sexual hormone effects of DIBA based on the expression levels of genes that respond to endocrine disruption and sexual hormone activity in the livers and gonads, and on gonadal sexual differentiation in Japanese medaka. Compared with the control group, the mRNA expression of chgH, vtg1, vtg2, and esr1 was significantly suppressed in the livers of DIBA exposed XX individuals. Furthermore, the mRNA expression of gsdf was significantly upregulated and downregulated in the gonads of XX and XY individuals, respectively. The mRNA expressions of esr1 and esr2b were significantly suppressed by DIBA exposure in the gonads of both XX and XY individuals. These observations suggest that DIBA has potential androgenic activity in Japanese medaka. However, normal testes and ovaries were observed in respective XY and XX medaka after DIBA exposure; therefore, these results suggest that DIBA may have weak androgenic activity. © 2024 Elsevier Inc.